DiN KiŞiSEL VE SOSYAL BiR iHTiYAÇTIR - Oruç, Cemil (Fırat University, 2008)
Religion has an important position in human beings life. Therefore, human beings has communicated with his creator. Because the faith was put into place the human's heart with his birth. Religion, aims the human beings happim;s. Religion has a powerful spiritual capital for happines, peace, integration and development. If we understand this power as true, the problems will be solved.
Religion is an lndividual and Social Necessity
Keywords: Religious Studies; Din Araştırmaları